Olive pomace as spreadable pulp: A new product for human consumption - Zina Guermazi; Cinzia Benincasa (AIMS Agriculture and Food, 2018)
In this study, the surface response methodology was used to determine the best conditions for the debitter of olive pomaces obtained from the extraction of olive oils in order to make them more palatable and acceptable to a group of selected tasters. According to the established model, the maximum response was 6.90. This response was obtained after 2.5 weeks of natural fermentation in a brine at pH of 5.57, temperature of 40 °C, sodium chloride concentration of 6/100 g of pastes. The idea was to produce a favorable environment to accelerate endogenous enzymes action and reduce the fermentation process time. Indeed, the brine was enriched with older brine, in the form of a lyophilized powder after deodorization, as it contains fermentable substrates and a large number of lactic acid bacteria. In addition, the olive pomace, by means of vapor water through a double wall membrane, was heated until reaching a temperature between 35 °C and 40 °C which presents the optimal temperature for the activation of oleuropein hydrolysis enzymes.